1999
DOI: 10.1021/ac981419z
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Devices Connected to Fused-Silica Capillaries with Minimal Dead Volume

Abstract: Fused-silica capillaries have been connected to microfluidic devices for capillary electrophoresis by drilling into the edge of the device using 200-μm tungsten carbide drills. The standard pointed drill bits create a hole with a conical-shaped bottom that leads to a geometric dead volume of 0.7 nL at the junction, and significant band broadening when used with 0.2-nL sample plugs. The plate numbers obtained on the fused-silica capillary connected to the chip were about 16-25% of the predicted numbers. The con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
188
1
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(191 citation statements)
references
References 22 publications
0
188
1
2
Order By: Relevance
“…Thus, Bings et al developed a method to obtain low deadvolume connectors, as small as 0.7 nL. 387 When the spray is generated from a transfer capillary, either a disposable nanospray emitter 388,389 or a fused-silica capillary transfer line can be inserted in the microchip. For the former, the ESI nozzle is usually made with a sharp, tapered capillary end from which the liquid sprays to produce small, well-defined droplets.…”
Section: Spraying From a Capillary Sprayer Attached To The Chipmentioning
confidence: 99%
“…Thus, Bings et al developed a method to obtain low deadvolume connectors, as small as 0.7 nL. 387 When the spray is generated from a transfer capillary, either a disposable nanospray emitter 388,389 or a fused-silica capillary transfer line can be inserted in the microchip. For the former, the ESI nozzle is usually made with a sharp, tapered capillary end from which the liquid sprays to produce small, well-defined droplets.…”
Section: Spraying From a Capillary Sprayer Attached To The Chipmentioning
confidence: 99%
“…The inlet and the outlet holes of the chips were subsequently enlarged by powder blasting [12]. Silica capillaries were inserted into these cavities using an in-house technique designed to minimize any dead volume, as suggested by Bings et al [13]. Epoxy glue (EPOTEK 353 NDT) was used to ®x the capillaries in their position.…”
Section: Microchipsmentioning
confidence: 99%
“…One of the challenges of chip-MS is the development of a stable and effective interface. The existing chip-ESI-MS interfaces use one of the following approaches: (1) spraying directly from the edge of a chip, [10,11] (2) spraying from a chip-inserted fused-silica capillary [12,13] and (3) spraying from a chip-integrated (microfabricated) ESI-tip. [14 -16] For interfacing on-chip separation techniques like capillary electrophoresis or liquid chromatography (LC) to MS, the critical point of all interfacing methods is the associated dead volume.…”
Section: Introductionmentioning
confidence: 99%
“…Harrison's group has shown that even small dead volumes can significantly decrease the separation performance by post-column band broadening. [12,13] Most of the chip-MS systems described in the literature contain ESI-tips made from fused-silica capillaries that were attached after microchip fabrication. [8,9] There is, however, a growing number of MS chips with integrated ESI-tips.…”
Section: Introductionmentioning
confidence: 99%